Peran Pekerja Sosial Terhadap Kemandirian Sosial Penyandang Disabilitas Mental di Yayasan Panti Rehabilitasi Mental Al-Hafizh Sidoarjo - Hawa Attin Syabaini; Sjafiatul Mardliyah (J+PLUS UNESA, 2026)
This study aims to analyze the role of social workers as educators in fostering the social independence of individuals with mental disabilities at the Al-Hafizh Mental Rehabilitation Foundation Sidoarjo, examine the supporting and inhibiting factors, and describe the form of social independence achieved by service recipients. This study employed a qualitative approach with a case study design. The informants consisted of foundation leaders, social workers, skills and sports instructors, religious guides, and individuals with mental disabilities undergoing rehabilitation. Data were collected through in-depth interviews, non-participatory and participatory observations, and documentation analysis, and were analyzed using Miles, Huberman, and Saldana's interactive model comprising data condensation, data display, and conclusion drawing. Data validity was tested through source and technique triangulation, extended observation, and member checks. The results revealed that social workers perform their educator role through habituation of daily living activities, structured vocational skill training such as slipper-making and batik ciprat, Ling Tien Kung therapy gymnastics, and spiritual guidance. Supporting factors include strong foundation managerial support, diverse program availability, interprofessional collaboration, clients' internal motivation, and adequate facilities. Inhibiting factors encompass unstable mental conditions, lack of family support, varying learning abilities, low initial motivation, and public stigma. Social workers' educational interventions significantly enhance clients' self-care capabilities, social interaction, teamwork, and readiness for community reintegration.